Impact of national-scale targeted point-of-care symptomatic lateral flow testing on trends in COVID-19 infections and hospitalisations during the second epidemic wave in Austria - Reitzinger, S; Czypionka, T; Leber, W; Panovska-Griffiths, J; Lammel, O (European Publishing, 2023)
Background: In October 2020, amidst the second COVID-19 epidemic wave and before the second-national lockdown, Austria introduced a policy of population-wide point-of-care lateral flow antigen testing (POC-LFT). This study explores the impact of this policy by quantifying the association between trends in POC-LFT-activity with trends in PCR-positivity (as a proxy for symptomatic infection) and hospitalisations related to COVID-19 between October 22 and December 06, 2020. Methods: We stratified 94 Austrian districts according to POC-LFT-activity (number of POC-LFTs performed per 100,000 inhabitants over the study period), into three population cohorts: (i) high(N=24), (ii) medium(N=45) and (iii) low(N=25). Across the cohorts we a) compared trends in POC-LFT-activity with PCR-positivity and hospital admissions; and, b) compared the epidemic growth rate before and after the epidemic peak. Results: The trend in POC-LFT activity was similar to PCR-positivity and hospitalisations trends across high, medium and low POCLFT activity cohorts. Compared to the low POC-LFT-activity cohort, the high-activity cohort had steeper pre-peak daily increase in PCR-positivity (2.24 more cases per day, per district and per 100,000 inhabitants; 95% CI: 2.0-2.7; p<0.001) and hospitalisations (0.10; 95% CI: 0.02, 0.18; p<0.15), and 6 days earlier peak of PCR-positivity. The high-activity cohort also had steeper daily reduction in the post-peak trend in PCR-positivity (-3.6; 95% CI: -4.8, -2.3; p<0.001) and hospitalisations (-0.2; 95% CI: -0.32, -0.08; p<0.05). Conclusions: High POC-LFT-use was associated with increased and earlier case finding during the second Austrian COVID-19 epidemic wave, and early and significant reduction in cases and hospitalisations during the second national lockdown. A national policy promoting symptomatic POC-LFT in primary care, can capture trends in PCR-positivity and hospitalisations. Symptomatic POC-LFT delivered at scale and combined with immediate self-quarantining and contact tracing can thus be a proxy for epidemic status, and hence a useful tool that can replace large-scale PCR testing.